k=(j>5)?(i<5)?i-j:j-i:k-j; i-=(k)?(i)?(j)?:(i):(k);

What will be the result of execution?

Answer: Option [D]

Given that the values of i,j and k are 8, 5 and 0 respectively. The first statement j>5 is not executed because j=5 and i<5 is also not executed. So the program evaluate k-j, which is, 0-5=-5. So afetre execution of first expression the values are 8, 5 and -5 respectively.

In the second statement the values of k, i are non zero. so it is true for both. So the values of i, j and k are 3, 5 and -5